2012
DOI: 10.1302/0301-620x.94b12.29357
|View full text |Cite
|
Sign up to set email alerts
|

The safety of peri-articular local anaesthetic injection for patients undergoing total knee replacement with autologous blood transfusion

Abstract: Intra-operative, peri-articular injection of local anaesthesia is an increasingly popular way of controlling pain following total knee replacement. At the same time, the problems associated with allogenic blood transfusion have led to interest in alternative methods for managing blood loss after total knee replacement, including the use of auto-transfusion of fluid from the patient's surgical drain. It is safe to combine peri-articular infiltration with auto-transfusion from the drain. We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“… 23 Based on pilot data, the standard deviation ( sd ) for VAS for pain was 30 mm. 24 Therefore, to test the null hypothesis of equality of the means of the treatment groups, assuming approximate normality for the VAS, primary outcome data for 264 patients (132 in each arm) were required for 90% power and 5% significance.…”
Section: Methodsmentioning
confidence: 99%
“… 23 Based on pilot data, the standard deviation ( sd ) for VAS for pain was 30 mm. 24 Therefore, to test the null hypothesis of equality of the means of the treatment groups, assuming approximate normality for the VAS, primary outcome data for 264 patients (132 in each arm) were required for 90% power and 5% significance.…”
Section: Methodsmentioning
confidence: 99%
“…Several published reports have demonstrated that plain local anesthetic shed into the prosthetic hip or knee joint following replacement does not lead to toxic serum levels following autotransfusion [19] , [20] , [29] , [30] . Parker et al [19] initially investigated this in 20 patients undergoing TKA who underwent autotransfusion of blood following PAI with ropivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…Only one other study to date assessed bupivacaine, specifically levobupivacaine, and its potential toxicity after autotransfusion of blood following TJA with PAI [30] . Levobupivacaine is an enatomer of bupivacaine that is reported to be less toxic and long lasting [31] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An initial pilot study comparing femoral nerve block and multimodal periarticular infiltration has already been completed in order to help plan and design a full trial with the following null hypothesis. 14 …”
Section: Introductionmentioning
confidence: 99%